The Association Between Work-life Balance and Employee Mental Health: A systemic review - Liswandi L; Rifqi Muhammad (ACHSM, 2023)
The existence of an association between work-life balance and mental health in employees has not been found. The purpose of the systematic review is to assess the relationship between work-life balance and mental health among employees. This study used the SLR method; a literature search was conducted on the PubMed, Scopus, Google Scholar, and Crossref databases in early January 2023. The results showed n = 79 on Scopus, n = 2 on PubMed, n = 147 on Google Scholar, and n = 4000 on Crossref. After PRISMA analysis, n = 30 studies were included in the review. Number of reviews Positive correlation between work-life balance and positive mental health (n = 19); positive correlation between work-life balance and positive mental health (n = 7); positive correlation between work-life imbalance and positive mental health (n = 4). Countries where research was conducted: Malaysia, South Korea, India, Indonesia, Pakistan, Spanish, Nigeria, Ghana, Australia, New Zealand Maori, China, UK, Chinese, New Zealand European, French, Italian, Brazil, Canada, Taiwan, Egyptian, Saudi, Switzerland, and America. Positive mental health variations that have a positive relationship with work-life balance are psychological well-being, resilience, life satisfaction, well-being, positive mental health, higher job satisfaction, lower turnover intention, psychological well-being, well-being, job performance, and work involvement. There are a variety of workers: priests, public servants, lecturers, campus administrative staff, bankers, high school teachers, academics, media workers, midwives, and professors. Depression, anxiety, mental burden, work stress, the severity of insomnia, burnout, turnover intention, and technostress are all variations of mental health problems that have a positive relationship with work-life balance. Worker variations include bankers, health care professionals, work-from-home moms, working students, bus transportation workers, and full-time insurance tech employees.